A novel 3D cell culture model to study the human small intestinal immune landscape. Issue 3 (3rd January 2023) - Schimpel, Christa; Passegger, Christina; Egger, Simone; Tam‐Amersdorfer, Carmen; Strobl, Herbert
Abstract: Several subsets of mononuclear phagocytes and DCs (MDC) populate the small intestine (SI), and these cells reportedly exert specialized functions in anti‐microbial immunity and tolerance. Given the specialized phenotype of these cells, differing from other MDC family members, including their putative circulating blood precursors, local intestinal factors play key instructive roles in their differentiation. We designed an SI cell culture model composed of three intestinal epithelial cell (IEC) types, including absorptive enterocytes (E cells), antigen delivering microfold (M) cells, and mucus‐producing goblet (G) cells plus T lymphocytes and soluble B cell‐derived factors. This model was used to study the differentiation fate of CD34 + hematopoietic progenitor cell‐derived monocyte/DC precursors. Progeny cells can be analyzed after a 3‐week co‐culture period, mimicking the physiologic turn‐over time of intestinal MDC. A dominant monocyte differentiation pathway was suppressed, in favor of partial differentiation along DC and macrophage pathways, with low percentages of cells acquired DC or macrophage markers. Moreover, E and G cells play opposing roles in CX3CR1 + vs CD103 dim cell differentiation, indicating that both together might counter‐balance M/DC differentiation. Thus, SI epithelial cells suppress M/DC differentiation, supporting a key role for exogenous factors in M/DC differentiation. Abstract : Our data indicate that enterocytes vs mucus‐secreting goblet cells play specialized roles in shaping the pre‐immune repertoire in the small intestine. A dominant monocyte differentiation pathway was suppressed, in favor of partial differentiation along DC and macrophage pathways, with low percentages of cells acquired DC (CD103 low CD209 low ) or macrophage markers (CD11b + CX3CR1 + ).